Implementation of Adiwiyata Program to Build Environmental Awareness - Rabiatul Adawiah (Center for Journal Management and Publication, 2019)
This study aims to find out the implementation of environmental caring and cultured (Adiwiyata) school program in Balangan Regency; (2) students’ attitude and behavior regarding environmental management and protection. This study uses a qualitative approach; the instruments used were interviews, observations, and questionnaires. The data analysis used an interactive model analysis of Miles and Huberman. The results show that the implementation of environmental caring and cultured school program in Balangan generally runs well, especially for environmental school policy, participatory based environmental activities, and management of environment supporting facility, nevertheles for environment based school curriculum development; there are some schools that have not implemented it holistically. Some teachers do not understand how to integrate the environment values into subject. Based on the findings of the students’ questionnaire, students’ attitude and behavior dealing with environmental management and protection are those that show 38.5% or very good attitude, 45% which means good attitude, and 12.5% referring to fairly good attitude, and 4% showing bad attitude.